Engagement Cancellation and Its Legal Implication In Malaysia (Woman’s Rights Perspective) - Fikriyah, Uswatul (Fakultas Syariah, 2015)
This article aims to describe the legal implication of engagement cancellation in Malaysia and to analyze the woman’s rights protection aspect in Act 303 Islamic Family Law Federal Territory 1984 in Malaysia. This article based on library research focuses on regulation Islamic Family Law Federal Territory Act 303 year 1984 of Malaysia, particularly concerning on about betrothal or Engagement. The result of this study show that the implication of engagement itself could open the opportunities to both of bride and groom to understand and know each other. The implications of engagement cancellation that can be taken from section 15 Act 303 Islamic Family Law Federal Territory. In Islamic family law in Malaysia especially Act 303 Federal Territory Islamic Family Law 1984 women have rights in accordance with their position, namely in the form of rights before marriage, the rights within marriage and the last is the rights after divorce. Women's rights protection aspects contained in the Act 303 Islamic Family Law Federal Territory generally not only in case of engagement cancellation or breach of promise of marriage (bethrothal) but in all the rights of women in marriage. It has the purpose to protect women's rights.